2004
DOI: 10.1523/jneurosci.3781-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal and Postrhinal Contributions to Remote Memory for Context

Abstract: The perirhinal (PER) and postrhinal (POR) cortices, two components of the medial temporal lobe memory system, are reciprocally connected with the hippocampus both directly and via the entorhinal cortex. Damage to PER or POR before or shortly after training on a contextual fear conditioning task causes deficits in the subsequent expression of contextual fear, implicating these regions in the acquisition or expression of contextual memory. Here, we examined the contribution of PER and POR to the processing of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 49 publications
(64 reference statements)
7
96
0
Order By: Relevance
“…In contrast, we found a long-lasting role for the LEC in memory retrieval, as LEC inactivation impaired expression of both recent (1-d-old) and remote (1-month-old) memories in trace eyeblink conditioning. This is consistent with findings of long-lasting retrograde memory impairments when large hippocampal lesions include the rhinal cortices in humans (Bayley et al, 2006) and primates (Suzuki et al, 1993), and with specific lesions to subregions of the rhinal cortices in rodents (Cho and Kesner, 1996;Burwell et al, 2004). Together, these findings suggest that the rhinal cortices play a long-lasting role in memory storage or retrieval.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, we found a long-lasting role for the LEC in memory retrieval, as LEC inactivation impaired expression of both recent (1-d-old) and remote (1-month-old) memories in trace eyeblink conditioning. This is consistent with findings of long-lasting retrograde memory impairments when large hippocampal lesions include the rhinal cortices in humans (Bayley et al, 2006) and primates (Suzuki et al, 1993), and with specific lesions to subregions of the rhinal cortices in rodents (Cho and Kesner, 1996;Burwell et al, 2004). Together, these findings suggest that the rhinal cortices play a long-lasting role in memory storage or retrieval.…”
Section: Discussionsupporting
confidence: 88%
“…Confirmation of these findings come from electrophysiological data which shows that there are different firing patterns observed in the perirhinal cortex during exposure to discontinuous tones compared to continuous tones (Furtak et al, 2007c) and from lesions of the perirhinal cortex where there is impairment of conditioning to ultrasonic vocalisations but not to continuous tones (Lindquist et al, 2004). These results fit with the data generated from recognition and fear conditioning tasks where the perirhinal cortex is required for processing more complex stimuli and contexts (Corodimas and LeDoux, 1995;Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Bussey et al, 2000;Eacott et al, 2001;Burwell et al, 2004a).…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningsupporting
confidence: 69%
“…Lesions of the rostral perirhinal cortex also lead to an attenuation of olfactory fear conditioning while sparing contextual fear conditioning Otto, 1997, 1998;Otto et al, 2000) and this sparing of contextual fear conditioning following perirhinal lesions has been confirmed by other groups (Phillips and LeDoux, 1995). However, other studies have shown that similar sized lesions in the same location (Corodimas and LeDoux, 1995) and larger ablations of the entire perirhinal cortex disrupt contextual fear conditioning (Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Burwell et al, 2004a). More generally temporary inactivation of the rostral perirhinal cortex seems to have an anxiolytic effect in an unconditioned fear task (Schulz-Klaus et al, 2005), this along with many of the above studies singling out the rostral region of the perirhinal cortex as being particularly important when it comes to emotional learning.…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningmentioning
confidence: 89%
See 2 more Smart Citations